New simplified approach for obtaining a reliable plateau value in fatigue analysis of bituminous materials - Subhy, Ayad; Lo Presti, Davide; Airey, Gordon (Elsevier, 2017)
The Plateau Value (PV) based on the Ratio of Dissipated Energy Change (RDEC) approach has been proven to provide a unique relationship with the fatigue life, Nf, independent of loading mode, temperature and frequency. In this paper, a new simplified approach is proposed to compute the unique energy parameter PV. The results of this study show that applying the proposed method allows a unique fatigue power law to be produced and eliminates the ambiguity and variability in calculating PV. However, the study also shows that the PV-Nf fatigue curves for bituminous materials are dependent on material type which is contradictory to other studies dealing with PV. The study also highlights the importance of appropriately identifying the fatigue failure point prior to commencing any fatigue analysis.